Impact of cosolvents on the interphase mass transfer on NAPLs in porous media - Yakış, Korcan. (Thesis (M.S.) - Bogazici University. Institute of Environmental Sciences, 2018., 2019)
Contamination of the subsurface with organic contaminants in the form of non-aqueous phase liquids (NAPLs) is a widespread and critical environmental threat. Due to their low aqueous solubilities, high adsorption rates and potentially high toxicities, these compounds act as long-term contamination sources and are among the most challenging to remediate. Conventional pump-andtreat techniques for the remediation of NAPLs have proven to be inefficient and cost-intensive. Among many remediation techniques introduced in the recent years, cosolvent flushing for enhanced dissolution of NAPLs is demonstrated as a cost-efficient and convenient method for in-situ remediation of NAPLs. Interphase mass transfer of the NAPL mass into the flushing solution is a key process that controls the effectiveness of the enhanced dissolution remediation technology; yet very few direct studies have rigorously investigated the effect of cosolvents on it. This study investigates the effect of cosolvents on the mass transfer of NAPLs into flushing solutions. The cosolvent and NAPL selected for this purpose are ethanol and 1,2-dicholorobenzene (DCB), respectively. A series of experiments are conducted to test the effect of ethanol content and flushing velocity on mass transfer. The experimental results are interpreted using a one-dimensional analytical solution and a two-dimensional pore network model. The mass transfer coefficients estimated from the two models are used to develop Sherwood correlations. It is observed that cosolvent presence has a significant impact on mass transfer coefficient. The developed Sherwood correlations can potentially be used in further modeling studies and field applications involving the remediation of entrapped NAPLs.
Keywords: Nonaqueous phase liquids.; Organic water pollutants.